Effects of Pollen Allergy on Pulmonary Function Tests - Syed Muarraf Hussain , Saadat Ali Khan,Syeda Maria Ali , Syed Irfan Ahmed ,Nelofar Jamil, (Journal of Rawalpindi Medical College, 2013)
Background: To investigate the effect of high air-borne pollen count on respiratory system. Methods: This cross sectional (descriptive) study included sixty known asthmatics, of either sex and of all ages. Pollen count as per cubic meter was recorded daily during February to May as reported by meteorological department. History, clinical examination and lung function tests were recorded in each case. The Pulmonary Function Test (PFT) with pollen count of asthmatic patients was correlated. Results: The PFT of asthmatic patients were adversely affected significantly during pollen season. There was negative correlation of moderate strength with FEV1 in asthmatic patients with high air borne pollen count during the pollen season. Conclusion: Spirometry was shown to be an effective technique to study the pollen allergy problem in already asthmatic patients